Association of Major Depression With Risk of Ischemic Heart Disease in a Mega‐Cohort of Chinese Adults: The China Kadoorie Biobank Study - Na Liu; Xiong‐Fei Pan; Canqing Yu; Jun Lv; Yu Guo; Zheng Bian; Ling Yang; Yiping Chen; Tangchun Wu; Zhengming Chen; An Pan; Liming Li (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
Background Increasing evidence has suggested that major depression (MD) is associated with an increased risk of ischemic heart disease (IHD). We examined this association in Chinese adults using data from the China Kadoorie Biobank study. Methods and Results Over 0.5 million adults aged 30 to 79 years were followed from baseline interview (2004–2008) until December 31, 2013. Past year MD was measured with the modified Chinese version of Composite International Diagnostic Interview‐Short Form at baseline. Incident IHD cases were identified through linkage to related medical databases, and defined as having International Statistical Classification of Diseases and Related Health Problems 10th Revision codes of I20 to I25. Cox proportional hazards regression models were used to estimate hazard ratios and 95% CIs for the MD‐IHD association with adjustment for sociodemographic variables and established cardiovascular risk factors. During 3 423 542 person‐years of follow‐up, 24 705 incident IHD cases were documented. Higher IHD incidence was observed in participants with MD compared with those without (8.76 versus 7.21 per 1000 person‐years), and the multivariable‐adjusted hazard ratio was 1.32 (95% CI 1.15–1.53). Geographic location modified the association (P for interaction=0.005), and a positive association was observed in urban residents (hazard ratio 1.72; 95% CI 1.39–2.14) but not rural residents (1.13; 0.93–1.37). Compared with participants without depressive symptoms, the hazard ratio (95% CI) of IHD was 1.13 (1.04–1.23) for those with depressive symptoms only and 1.33 (1.15–1.53) for those with MD. Conclusions Past year major depression was associated with an increased risk of IHD in Chinese adults, independent of other major cardiovascular risk factors.